India's quest for a new worldview - Suryanarayana, Pisupati Sadasiva (2023)
In seeking a new worldview, India established a techno-strategic partnership with the United States in June 2023. Delhi also engaged China and Russia in the Shanghai Cooperation Organisation in July while preparing to host the leaders of the G20 countries in September. And with France recognising India’s relevance in future global governance, Delhi’s quest for a new worldview received a further boost.